Development of crowding-in as an alternative form of small and mediumsized businesses financing: foreign experience and Russian practice - K. V. Glukhov; M. V. Kulikov (Вестник университета)
The article presents a comprehensive analysis of legal and economic measures aimed at state support for small and medium-sized businesses in order for them to obtain an alternative source of financing using crowdinvesting platforms, and a consimilar foreign experience research. Based on statistical data, conclusions on the crowdinvesting platforms sector’s development and its interaction with small and medium-sized businesses are presented. Within the frameworks of the article, the emphasis is placed on a detailed study of foreign experience in the providing an alternative funding source. The advantages and disadvantages of this method in the Russian context have been shown. The study involved an analysis and synthesis of domestic and foreign anti-crisis measures.